KECERDASAN EMOSIONAL SISWA BERHUBUNGAN DENGAN PERILAKU BULLYING DI SEKOLAH - Agita Zunilatri Kurniastiti; Rahmah; Retno Sumiyarini (MEDIA ILMU KESEHATAN, 2014)
Background: Students should have emotional intelligence to control their emotion and to reduce bullying. By having good emotional intelligence, students will be able to understand themselves and others, so they can control their behavior. Eventually, they will be able to maintain a good relationship with their peers by not hurting others’ feeling or harming others physically. Objective: This research aimed to analyze the correlation between emotional intelligence and school bullying behavior in students in a Junior High School of Bantul Regency. Methodology: This research employed correlational quantitative method with cross sectional design. The samples were taken randomly, consisted of 92 students of grade VIII and IX. Data were analyzed using univariate and bivariate technique with Product Moment Correlation statistical test. Findings: The result of univariate analysis showed that students’ emotional intelligence was high as there were 51 students in this category (55,4%), and the behavior of school bullying was low (57,6%). Bivariate analysis using Product Moment correlation showed that the p-value was 0,001<α 0,05. The coefficient value of -0,571 showed that the level of emotion was moderate. Conclusion: There was a significant correlation between emotional intelligence and school bullying behavior in students in a Junior High School of Bantul Regency. Key words: Emotional intelligence, school bullying behavior